Study on the effect of synergy effect between the mixed cultures on the power generation of microbial fuel cells. Issue 1 (1st January 2021) - Ren, Jing; Li, Na; Du, Maohua; Zhang, Yixin; Hao, Chunxu; Hu, Rui
ABSTRACT: Microbial fuel cells (MFC) can use microorganisms to directly convert the chemical energy of organic matter into electrical energy, and generate electrical energy while pollutants degradation. To solve the critical problem of lower power yield of power production, this study selected Saccharomyces cerevisiae, Escherichia coli, Pseudomonas aeruginosa, and Bacillus subtilis as the anodic inoculums. The influence of the mixed bacteria on the power-producing effect of MFC and the synergy effect between the electrochemically active bacteria in mixed cultures were discussed. The results showed that among the mixed culture system, only the mixed cultures MFC composed of Saccharomyces cerevisiae and Bacillus subtilis had a significant increase in power generation capacity, which could reach to 554 mV. Further analysis of the electrochemical and microbiological performance of this system was conducted afterward to verify the synergy effect between Saccharomyces cerevisiae and Bacillus subtilis . The riboflavin produced by Bacillus subtilis could be utilized by Saccharomyces cerevisiae to enhance the power generation capacity. Meanwhile, Saccharomyces cerevisiae could provide carbon source and electron donor for Bacillus subtilis through respiration. Finally, in the experiment of adding exogenous riboflavin in the mixed bacterial MFC, the result indicated that the mixed bacterial MFC chose the self-secreting riboflavin over the exogenous riboflavin as the electron mediator, and the excess riboflavin might hinder the electron trasfer. Graphical abstract: uf0001